Predictors of Early (0-7 Days) and Late (8-30 Days) Readmission in a Cohort of Acute Coronary Syndrome Patients - George Cholack; Joshua Garfein; Rachel Krallman; Delaney Feldeisen; Daniel Montgomery; Eva Kline-Rogers; Geoffrey D. Barnes; Kim Eagle; Melvyn Rubenfire; Sherry Bumpus (International Journal of Medical Students, 2022)
Background: Readmissions following acute coronary syndrome are unevenly distributed across the 30-day post-discharge period. There is limited data on predictors of all-cause readmission in early (0-7 day) and late (8-30 day) post-discharge periods for this population; the purpose of this retrospective cohort study was to identify predictors of early and late readmission.